Sentimentalism in nineteenth-century America : literary and cultural practices (Fairleigh Dickinson University Press ; Co-published with The Rowman and Littlefield Publishing Group, Incorporated, 2013)
Tracing the eighteenth-century origins of sentimentalism, the collection illustrates its proliferation in nineteenth-century America. Sentimental writings by both sexes played a major role in the formation of middle-class culture and identity as sentimentalism interacted with developing ideals of domesticity, reform movements, and nationhood. Contributors explore motherhood, education, reform, loss and mourning, and the Civil War's explosion of the faith in universal feelings and ideas on which sentimentalism was based. ("Both sexes" is an impo